2014
DOI: 10.1038/modpathol.2013.167
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the TERT promoter are common in basal cell carcinoma and squamous cell carcinoma

Abstract: Telomerase is frequently expressed in cancer and contributes to carcinogenesis. Two recent publications report the identification of a set of recurrent mutations in melanoma in the promoter of the telomerase reverse transcriptase gene (TERT) that appears to be the result of mutagenesis from ultraviolet (UV) radiation. Both groups reported that the mutations increase the transcription of TERT. This prompted our search for similar mutations in two other UV-related skin cancers, basal cell carcinoma, and squamous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 23 publications
8
81
1
Order By: Relevance
“…Seven cases carried the C228T mutation, which also is the most frequently mutated site in other cancers [9]; C250T was found only in homozygosity in one MCL sample. Those two out of eight mutant cases were homozygous that is relevant, given that homozygosity for TERTp mutations is very rare and was only previously described in basal cell and squamous cell carcinomas [21]. In a series of 1,230 samples from 60 different tumor types, all identified TERTp mutations were in heterozygosity and were mutually exclusive [9].…”
Section: Discussionmentioning
confidence: 78%
“…Seven cases carried the C228T mutation, which also is the most frequently mutated site in other cancers [9]; C250T was found only in homozygosity in one MCL sample. Those two out of eight mutant cases were homozygous that is relevant, given that homozygosity for TERTp mutations is very rare and was only previously described in basal cell and squamous cell carcinomas [21]. In a series of 1,230 samples from 60 different tumor types, all identified TERTp mutations were in heterozygosity and were mutually exclusive [9].…”
Section: Discussionmentioning
confidence: 78%
“…We and others reported the presence of recurrent somatic mutations in the telomerase promoter in cancers of the central nervous system (43-51 %), bladder (59-66 %), hepatocellular carcinoma (59 %), thyroid (follicular cell-derived tumours) (10 %), skin (melanoma, 29-73 %) and tumours originated from tissues with relatively low rates of self-renewal [58,75,88,121]. Additionally, other studies reported the association of telomerase promoter mutations to other types of tumours, including atypical fibroxantoma (93 %), pleomorphic dermal sarcoma (76 %) [39], bladder cancer (65 %) [1,54], basal cell carcinoma (78 %), squamous cell carcinoma of the skin (50 %) [110] and clear cell carcinoma of the ovary [124]. In Tables 2 and 3, we summarize the frequency of TERT promoter mutations in human cancers with a high percentage of mutations and in human cancers with absent or low frequency of TERT promoter mutations, respectively.…”
Section: Telomerase Promoter Mutations and Cancermentioning
confidence: 99%
“…TERT promoter mutations are frequent in non-melanoma skin cancer, ranging from 39 to 74 % in sporadic basal cell carcinomas (BCC) [37,94,110] and present in up to 50 % of cases of squamous cell carcinoma (SCC) [3 7, 110].Telomerase activity has been detected in BCC using TRAP assay both in tumour and tumour-free margins, varying between 20 and 100 %, with less activity in the latter [29]. In the tumour-free margins, telomerase activity was found to be more prevalent in sun-exposed skin [105,119].…”
Section: Telomerase Promoter Mutations In Skin Cancersmentioning
confidence: 99%
“…Shortly after, several groups reported the presence of recurrent somatic mutations in other types of cancer, namely in central nervous system, bladder, liver, thyroid, skin and others (Killela et al 2013, Liu et al 2013a, Nault et al 2013, Scott et al 2013, Vinagre et al 2013, Allory et al 2014, Hurst et al 2014, Wu et al 2014.…”
Section: Introductionmentioning
confidence: 99%